A Collaborative Architecture to support Circular Economy through Digital Material Passports and Internet of Materials. Issue 10 (2022) - Panza, Luigi; Bruno, Giulia; Lombardi, Franco
Abstract: Circular Economy is regarded to be a suitable strategy to achieve the sustainable production and consumption of the Earth's resources. However, the effective implementation of the Circular Economy requires information about materials throughout the lifecycle phases. This paper provides a framework for the material lifecycle digitization through the establishment of the digital material passport. The latter born together with the physical material at the sourcing phase, and flow with it in all the lifecycle phases. Examples of information to be stored in the digital passport of materials are provided. To foster more sustainable and circular products, a digital network of material passports is needed, the Internet of Materials, which would act as an eco-collaborative platform that assists designers and engineers during the product development activity. Requirements, effects, and challenges of such platform are discussed.